BUDAYA LITERASI PADA ANAK USIA DINI ERA SOCIETY 5.0 DI PANTI ASUHAN RUMAH ANAK HARAPAN GUNUNGSITOLI - Waruwu, Lestari; Imansudi Zega; Mastawati Ndruru (Jurnal Abdi Masyarakat Multidisiplin, 2024)
Through this Community Service Activity aims to provide understanding and knowledge to early childhood in the Rumah Anak Harapan Orphanage (RANAH) in Gunungsitoli City. In this Community Service Activity involved 3 lecturers and several students as participants who accompanied and all the children who dated at the Rumah Anak Harapan Orphanage (RANAH). Cultivating a culture of literacy in children needs to be instilled early, because at that age children enter the golden period or often called the golden age. Early childhood is a child aged zero to six years, during this period the child experiences very rapid development and growth, so that the habits that children do from an early age will also become habits when children grow up. The results obtained from PkM activities which have been carried out face-to-face using the lecture method are: (1) Early childhood reading literacy, writing literacy and student creativity have increased, (2) Understanding of breastfeeding home managers regarding literacy activities in schools has increased, (3) The Orphanage management continues to try to find information related to literacy activities. (4)t Establishment of a Cooperation Agreement (PKS) between the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Nias University and the Rumah Anak Harapan Orphanage (RANAH).